Synthesis and Biological Activity of 2-Aryloxyacetylamino-2-Deoxy-D-Glucoses - Han, Liang; Zhu, Qiong-Yan; Jia, Jian-Hong; Li, Yu-Jin; Gao, Jian-Rong (Asian Journal of Chemistry, 2011)
D-Glucosamine possesses extensive bioactivities including antibacterial, insecticidal and plant growth-regulating activities. A series of 2-aryloxyacetylamino-2-deoxy-D-glucoses have been synthesized by acylation of D-glucosamine with aryloxyacetyl chlorides and their plant growthregulating activities were tested. The results show that these compounds bearing chlorine atom at para position of benzene ring have notable inhibiting activities against cotyledon rootage of cucumber which are comparable with that of 2,4-dichlorophenoxyacetic acid.